Development of bio-yoghurt chewable tablet: a review - Chan, Yong Lin; Jamalullail, Nurul Aini; Tan, Chin Ping; Abdul Manap, Mohd Yazid; Lai, Oi Ming (Emerald Publishing Limited, 2020)
Purpose - This paper aims to discuss the limitations surrounding the yoghurt industry and challenges to producing a bio-yoghurt tablet. The paper looks into challenge facing the yoghurt industry, such as manufacturing and distribution, its short shelf life, heat-sensitivity and relatively heavy weight. It further looks into the selection of strains, excipients and storage conditions with special consideration towards maintaining the viability of the probiotics inside bio-yoghurt tablets. The paper also discusses yoghurt standards and definitions across various countries and suggests a more uniform standard be embraced across countries for ease of categorization and production. Design/methodology/approach – The paper is divided into a few major sections; each exploring various aspects of the yoghurt industry. Topics discussed include challenges in yoghurt production and storage; processes involved in bio-yoghurt tablet production, e.g. maximising viability, choice of excipients and more; market trends of yoghurt consumption and potential; and various food standards in countries around the world with a focus on yoghurt. Findings – The review finds that yoghurt is a segment of the food industry with big growth potential. Most of the problems associated with yoghurt, i.e. poor shelf life, and heavy weight, can be circumvented by transforming it into a bio-yoghurt tablet. The paper further identifies food standard variations among different countries around the world which could impede yoghurt manufacture and acceptance. Originality/value – This paper looks the various challenges surrounding the increased uptake of yoghurt, specifically in the Asian markets and suggests a viable option to overcome this problem, i.e. the use of a bioyoghurt tablet. Should the worldwide bodies come together and agree to a universal standard involving yoghurt, the industry may see an even bigger expansion.